Transmission Properties of Metallic Grating with Subwavelength Slits in THz Frequency Region - Dong Liang; Qirong Xing; Zhen Tian; Changlei Wang; Weili Zhang; Jianqiang Gu; Yanfeng Li; Lu Chai; Qingyue Wang; Aleksei Zheltikov (Active and Passive Electronic Components)
This paper presents a fully experimental and theoretical study on transmission properties of a deep metallic grating with subwavelength slits in THz frequency region by using THz time domain spectroscopy (THz-TDS). The grating exposed to p-polarized incident wave exhibits enhanced nonresonant transmission in the long-wavelength region where the incident wavelength is larger than the grating period. Wood anomalies are observed when the wavelength is comparable to the grating period. Strict theory is given to explain the experimental results and the two are in good agreement. It is proposed that the Wood dips may be considered a criterion and a tool to judge and control the uniformity or fabricating accuracy of the grating period.